2012
DOI: 10.2466/10.25.27.pms.115.4.171-178
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between Three Fine Motor Skills in Young Adults

Abstract: Motor skills are typically considered to be highly specific, although some researchers have attempted to identify evidence for general motor aptitude. The present study tested these contentions by assessing the extent of relationship between fine motor tasks, using correlations between selected performance measures for three fine motor skills. University students ages 18 to 35 years (N = 305; 147 men, 158 women) completed three fine motor tasks with both right and left hands (placing pegs, posting coins, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…For example, within-trial individual variability can be more substantial in motor tasks compared with cognitive tasks (Lövdén, Schaefer, Pohlmeyer, & Lindenberger, 2008), which suggest that reliability statistics both within and between performance domains are not necessarily comparable. Assessment of motor performances is particularly prone to substantial inter and intra-individual variability that, among other things, can display as low correlations between different motor tasks (Haga, Pedersen, & Sigmundsson, 2008;Lorås & Sigmundsson, 2012). Held against this background, we are inclined to conclude that our obtained ICCs (≥.75) suggest relatively low degree of variation in test-retest of the subtests/total score.…”
Section: Reliability Of the Test Batterymentioning
confidence: 70%
“…For example, within-trial individual variability can be more substantial in motor tasks compared with cognitive tasks (Lövdén, Schaefer, Pohlmeyer, & Lindenberger, 2008), which suggest that reliability statistics both within and between performance domains are not necessarily comparable. Assessment of motor performances is particularly prone to substantial inter and intra-individual variability that, among other things, can display as low correlations between different motor tasks (Haga, Pedersen, & Sigmundsson, 2008;Lorås & Sigmundsson, 2012). Held against this background, we are inclined to conclude that our obtained ICCs (≥.75) suggest relatively low degree of variation in test-retest of the subtests/total score.…”
Section: Reliability Of the Test Batterymentioning
confidence: 70%
“…Significant empirical evidence now exists supporting the notion that learning is specific. For example, the correlation between different motor tasks are generally low [ 50 , 51 , 52 , 53 , 54 ]. Drowatzky and Zuccato [ 52 ] provided support for the specificity of learning some time ago when they found only very low correlations (0.03 to 0.31) between six different balance exercises.…”
Section: The Learning Processmentioning
confidence: 99%
“…In other words, improvement in one motor skill does not ensure improvement in other motor skills. This hypothesis is supported by empirical studies showing low correlations between individual motor skill items in children (Haga et al, 2008;Lorås and Sigmundsson, 2012;Stöckel and Hughes, 2016;Gísladóttir et al, 2019). For example, Haga et al (2008) found mostly no or non-significantly weak correlations between items of the Movement Assessment Battery for Children in 4-year-old children.…”
Section: Introductionmentioning
confidence: 73%